2008
DOI: 10.4141/cjas07129
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of carbon dioxide production and energy expenditure of grazing cattle by the sulphur hexafluoride (SF6) tracer gas technique

Abstract: . 2008. Estimation of carbon dioxide production and energy expenditure of grazing cattle by the sulphur hexafluoride (SF 6 ) tracer gas technique. Can. J. Anim. Sci. 88: 651Á 658. The purpose of the study was to explore the suitability of the sulphur hexafluoride (SF 6 ) tracer gas technique to estimate CO 2 production and energy expenditure (EE) for grazing animals on pastures typical of western Canada. During each year of a 3-yr study, CO 2 emissions were collected from 60 yearling steers on grass pastures r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In comparison, the steers in the current study were heavier (577 kg BW), had higher DMI (13.3 kg/d), and produced proportionally higher CPR (8939 g/d) and CY (679 g/kg). There have been some CPR studies (Boadi et al, 2002;Pinares-Patiño et al, 2007;Stewart et al, 2008) on grazing cattle using the sulphur hexafluoride (SF 6 ) tracer-gas technique. However, we could not compare our results with those studies as the SF 6 gas technique has been reported to overestimate individual animal CPR, although animal rankings are maintained relative to respiration chamber measurements (Boadi et al, 2002;Pinares-Patiño et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, the steers in the current study were heavier (577 kg BW), had higher DMI (13.3 kg/d), and produced proportionally higher CPR (8939 g/d) and CY (679 g/kg). There have been some CPR studies (Boadi et al, 2002;Pinares-Patiño et al, 2007;Stewart et al, 2008) on grazing cattle using the sulphur hexafluoride (SF 6 ) tracer-gas technique. However, we could not compare our results with those studies as the SF 6 gas technique has been reported to overestimate individual animal CPR, although animal rankings are maintained relative to respiration chamber measurements (Boadi et al, 2002;Pinares-Patiño et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Alternative techniques to respiratory chambers are enabling scientists to collect or record gas measurements from cattle in their own production settings (e.g., grazing, free stall). Specific examples include quantifications of (1) heat production (HP) from O 2 consumption per heartbeat (Brosh et al, 1998;Aharoni et al, 2006), (2) energy expenditure using the 13 C bicarbonate technique coupled with O 2 consumption and respiratory quotient (RQ; Junghans et al, 2007;Kaufmann et al, 2011), (3) carbon emissions using tracer techniques (Stewart et al, 2008;Madsen et al, 2010), and (4) CO 2 flux (QCO 2 ) and CH 4 flux (QCH 4 ) in animal breath (Branco et al, 2015;Dorich et al, 2015;Huhtanen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%